Pengaruh Pemberian Edukasi tentang Penyakit Diabetes Melitus terhadap Motivasi Pengobatan Penderita Diabetes Melitus di Puskesmas Mranggen 2 - Fina Ayu Kusuma; Iwan Ardian; Nutrisia Nu’im Haiya (Journal of Medical Practice and Research, 2025)
Diabetes Mellitus is a chronic disease that requires long-term management. Low treatment motivation among patients often becomes an obstacle to successful therapy. Educational interventions have been shown to improve patients’ understanding and motivation in undergoing treatment. To determine the effect of diabetes education on treatment motivation among patients with Diabetes Mellitus. This study employed a quantitative design using a one-group pre–post test model. A total of 83 respondents were selected using purposive sampling. The instrument used was a motivation questionnaire that had been tested for validity and reliability. Data were analyzed using the Wilcoxon Signed Rank Test (α = 0.05). Most respondents had moderate motivation before receiving education (98.8%), while only a small proportion had low motivation (1.2%). After the educational intervention, motivation increased, indicated by the rise in the high-motivation category to 41.0% and the decrease in the moderate category to 59.0%. Comparison of pretest and posttest scores showed that 67.5% of respondents experienced increased motivation, 24.1% experienced a decrease, and 8.4% showed no change. The Wilcoxon test produced a significance value of 0.000 (p < 0.05), indicating a significant difference between motivation before and after education.